Substituição parcial do cimento CPV-ARI por do lodo de estação de tratamento de água (ETA) - Alexandre, Elisandro (2018)
The sludge generated during the water treatment process to supply the population is discarded in most of the time, without adequate treatment in the water bodies, causing negative environmental impacts to the environment. In this context, the study carried out the evaluation of ETA sludge for the partial replacement of Portland cement of high initial resistance (CPV-ARI). Initially the CPV-ARI was partially replaced with 10% and 20% of sludge ETA in slurry, and the slurry was cured at environment temperature of 23°C for up to 28 days. The mechanical resistance and the hydrated compounds were evaluated, tests of XRD, TG/DTG and MEV, as well as conduction calorimetry. The replacement of CPV-ARI cement with ETA sludge reduced the mechanical strength capacity when compared to the reference paste for the age of 7 days. With increasing age, all samples suffered an increase in mechanical resistance. It can be observed the incorporation of the compounds present in the ETA sludge by the cement compounds. The results obtained show that the use of ETA sludge in the cement composition is a viable alternative to the environmentally correct fate of the sludge without significantly losing the properties of the CPV-ARI cement.